Increased thrombin generation potential in symptomatic versus asymptomatic moderate or severe carotid stenosis and relationship with cerebral microemboli. Issue 4 (17th July 2014) - Kinsella, J A; Tobin, W O; Kavanagh, G F; O'Donnell, J S; McGrath, R T; Tierney, S; Feeley, T M; Egan, B; O'Neill, D; Collins, D R; Coughlan, T; Harbison, J A; et al.
Abstract : Introduction: The importance of thrombin generation in the pathogenesis of TIA or stroke and its relationship with cerebral microembolic signals (MES) in asymptomatic and symptomatic carotid stenosis has not been comprehensively assessed. Methods: Plasma thrombin generation parameters from patients with moderate or severe (≥50%) asymptomatic carotid stenosis were compared with those from patients with symptomatic carotid stenosis in the early ( ≤4 weeks) and late phases (≥3 months) after TIA or stroke in this prospective, pilot observational study. Thrombin generation profile was longitudinally assessed in symptomatic patients with data at each time point. Bilateral transcranial Doppler ultrasound monitoring of the middle cerebral arteries was performed whenever possible to classify patients as MES-positive or MES-negative. Results: Data from 31 asymptomatic, 46 'early symptomatic' and 35 'late symptomatic' patients were analysed. Peak thrombin (344.2 nM vs 305.3 nM; p=0.01) and endogenous thrombin potential (1772.4 vs 1589.7; p=0.047) were higher in early symptomatic than asymptomatic patients. Peak thrombin production decreased in symptomatic patients followed up from the early to late phase after TIA or stroke (339.7 nM vs 308.6 nM; p=0.02). Transcranial Doppler ultrasound data were available in 25 asymptomatic, 31 early symptomatic and 27 late symptomatic patients. Early symptomatic MES-positive patients had a shorter 'time-to-peak thrombin' than asymptomatic MES-positive patients (p=0.04), suggesting a more procoagulant state in this early symptomatic subgroup. Discussion: Thrombin generation potential is greater in patients with recently symptomatic than asymptomatic carotid stenosis, and decreases over time following TIA or stroke associated with carotid stenosis. These data improve our understanding of the haemostatic/thrombotic biomarker profile in moderate-severe carotid stenosis.